2019
DOI: 10.15252/embr.201847030
|View full text |Cite
|
Sign up to set email alerts
|

USP26 regulates TGF‐β signalling by deubiquitinating and stabilizing SMAD7; not applicable in glioblastoma

Abstract: Comment on “USP26 regulates TGF‐β signaling by deubiquitinating and stabilizing SMAD7” by Kit Leng Lui et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
3
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
2
3
0
Order By: Relevance
“…Leng Lui et al [3]). These findings are in agreement with those presented by Ware and colleagues, where they indicate that, "Our findings agree with the authors reported trend with low USP26 expression conferring to poorer prognosis, although the effect on survival is minor and the clinical relevance remains unclear" [2]. Furthermore, we have now analysed USP26 expression in the most recent TCGA GBM cohort from cBioPortal (TCGA GBM, mRNA RNA-seq v2 RSEM data, z score 2 threshold 1.0, n = 166).…”
Section: Fig 5d In Kitsupporting
confidence: 94%
See 2 more Smart Citations
“…Leng Lui et al [3]). These findings are in agreement with those presented by Ware and colleagues, where they indicate that, "Our findings agree with the authors reported trend with low USP26 expression conferring to poorer prognosis, although the effect on survival is minor and the clinical relevance remains unclear" [2]. Furthermore, we have now analysed USP26 expression in the most recent TCGA GBM cohort from cBioPortal (TCGA GBM, mRNA RNA-seq v2 RSEM data, z score 2 threshold 1.0, n = 166).…”
Section: Fig 5d In Kitsupporting
confidence: 94%
“…In line with our previous results, we demonstrate that low USP26 expression is associated with poorer overall survival in glioblastoma, at the median threshold (high vs low), showing statistical significance with an overall P-value of 0.0259 (REMBRANDT) (new [3]). These findings are in agreement with those presented by Ware and colleagues, where they indicate that, "Our findings agree with the authors reported trend with low USP26 expression conferring to poorer prognosis, although the effect on survival is minor and the clinical relevance remains unclear" [2]. Furthermore, we have now analysed USP26 expression in the most recent TCGA GBM cohort from cBioPortal (TCGA GBM, mRNA RNA-seq v2 RSEM data, z score 2 threshold 1.0, n = 166).…”
supporting
confidence: 94%
See 1 more Smart Citation
“…The journal notes the following issues: Figure 5A reported a statistically significant negative correlation between USP26 and phospho-SMAD2 levels in tissue microarrays from human glioblastoma patients (r = À0.15, P < 0.0001). In response to comments from Thomas MB Ware and Hong-Jian Zhu [2], the authors have provided a re-analysis of their data demonstrating that no significant correlation exists between the expression of these two proteins (r = À0.15, P = 0.18).…”
mentioning
confidence: 99%
“…Metastasis is the main cause of cancer-related deaths for breast cancer patients. 1 3 Transforming Growth Factor-beta (TGF-β) and its signaling pathway are major drivers of metastasis 3 5 and increased TGF-β signaling activity is associated with reduced survival for breast cancer patients. 6 , 7 Accordingly, therapeutics, such as the TGF-β receptor Type I (TβRI) kinase inhibitor SB431542, have been developed to target the TGF-β signaling for treatment of human diseases, including cancer.…”
Section: Introductionmentioning
confidence: 99%